Unraveling the meiotic puzzle: chromosome count, meiotic behaviour, and reproductive challenges in Phlomis cashmeriana Royle ex Benth. from the Kashmir Himalaya - Qadir, Roof Ul; Javid, Hanan; Ganie, Aijaz Hassan; Wani, Bilal A.; Nawchoo, Irshad A.; Magray, Junaid A. (Frontiers in Conservation Science, 2025)
Meiotic stability is crucial for maintaining reproductive success and genetic diversity in plants, especially in montane regions like the Himalaya, where fluctuating environmental conditions can disrupt normal chromosome behavior. Phlomis cashmeriana Royle ex Benth., a medicinally important species, has not previously been studied for the meiotic behavior and its impact on reproductive output. This study presents the first comprehensive meiotic analysis of P. cashmeriana across three populations in the Kashmir Himalaya, focusing on chromosome count, meiotic behavior, pollen fertility, and seed set. While most of the Pollen Mother Cells (PMCs) exhibited normal meiosis, several meiotic abnormalities were recorded, including chromosome stickiness, laggards, unoriented bivalents, and interchromosomal connections. Chromosome stickiness (11.48%) was the most prominent abnormality, particularly during diakinesis and metaphase I across all the study sites. These irregularities, likely influenced by high UV radiation and low temperatures characteristic of the region, were associated with reduced pollen viability (67.65–74.50%) and seed set (54.40–59.75%) across the studied populations. Such reproductive impairments may compromise the long-term survival and genetic resilience of P. cashmeriana, potentially limiting its adaptive capacity under ongoing changing environmental conditions. These findings highlight the broader ecological significance of meiotic behavior as a determinant of reproductive fitness and evolutionary potential in Himalayan flora. Understanding these cytological constraints is vital for developing informed, long-term conservation and management strategies for P. cashmeriana and other threatened montane species. Future research should explore the genetic basis of these abnormalities and assess population viability under shifting climate conditions.